The Effect of Self-efficacy on Acquiring Innovation Ideas among Food Vendors - Akolgo, Isaac Gumah; Li, Cai; Udimal, Thomas Bilaliib; Dodor, Ann; Adomako, Kankam William (International Review of Management and Marketing, 2019)
The study aims at assessing the effect of self-efficacy on acquiring innovation ideas among food vendors in Zhenjiang. The study employed a cross sectional design with a sample size of 400 food vendors as the study participants. Quantitative data were collected from the participants through surveys. The data were analysed through the use of AMOS 23.0 software. The findings of the study revealed that food vendors acquired their innovative ideas through learning from parental, mentor and television models. The findings indicated that food vendors acquired innovative ideas about the cuisine industry from parents, television and mentors. The findings revealed that self-efficacy boosted the relationship between parental model and innovation. The findings further revealed that self-efficacy mediated the relationship between television model and innovation. The findings of the study have contributed to deepening the understanding of entrepreneurs learning innovation. The study also enriches literature in the field of social learning and career development. The study therefore recommends that entrepreneurs build on enhancing their self confidence level so as to be innovative. The study also recommends that educational institutions should include programmes, courses, seminars and training which will improve students' individual self-confidence. Keywords: Food vendors, innovation ideas, self-efficacy, entrepreneurship, vicarious learning JEL Classifications: L26, L66, O3 DOI: https://doi.org/10.32479/irmm.8340